Pengaruh Kontrak Pemerintah Terhadap Penilaian Perusahaan - Sri Adina Sitepu (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2021)
Every company wants its high company value and can attract the attention of investors to make investments. In increasing company value, the company must be able to increase the supporting factors of the company value itself. One of the factors that can increase company value is government contracts. In the sense that if the company has a good cooperation with the company, the value of the company will be better in the eyes of investors. The purpose of this literature review is to see the effect of government contracts on firm value. The method in this literature review is a literature review. The search for review articles is carried out using the database of sciences from google scholar, scientific directory and clinical keys using keywords, namely government contracts (cooperation with the government) and company valuation: tobins Q (firm value), cost of equity (capital cost), profitability (profitability). ) and sales growth (sales growth). The results of the study found that government contracts have a lower responsibility than companies, government contracts have a statistically significant effect on lower equity. Companies that contract with the government have a significant negative effect on sales growth. Government contracts on industry are strategically more important to increase the value of profitability compared to industries that are not strategically important.